Are Advertising Agency Creatives More Creative Than Anyone Else? An Exploratory Test of Competing Predictions. Issue 2 (13th August 2020) - de Gregorio, Federico; Windels, Kasey
Abstract: This exploratory research tests two competing general predictions: the expert-performance literature predicting creatives will demonstrate greater creativity than others while the process-performance paradox literature predicting they will demonstrate equivalent or less creativity. We compare the performance of agency creatives with agency noncreatives and a general population sample on three creativity assessments: a general divergent thinking test (Alternative Uses Task), a general convergent thinking test (Remote Associates Test), and an advertising domain-specific creativity test (scenario-based tagline generation). Creatives did not outperform noncreatives on any of the tests but did outperform the general population in terms of the elaboration and originality aspects of divergent thinking. The general population outperformed both agency samples on the convergent thinking test. No differences were found in the domain-specific creativity test. Overall, this exploratory study finds more evidence supporting the process-performance paradox perspective.